High-altitude cerebral hypoxia promotes mitochondrial dysfunction and apoptosis of mouse neurons - Huan, Yu; Quan, Huilin; Jia, Bo; Hao, Guangzhi; Shi, Zuolin; Zhao, Tianzi; Yuan, Ying; Yuan, Fang; Dong, Yushu; Liang, Guobiao (Frontiers in Molecular Neuroscience, 2023)
Introduction Neuronal cell death is an important factor in the pathogenesis of acute high-altitude cerebral hypoxia; however, the underlying molecular mechanism remains unclear. In this study, we tested if high-altitude hypoxia (HAH) causes neuronal death and mitochondrial dysfunction using various in vivo and in vitro approaches. Methods Acute high-altitude cerebral hypoxia was induced by hypobaric hypoxia chamber in male mice. we explored the mechanisms of neuronal cell death using immunofluorescence, western blotting, transmission electron microscopy, and flow cytometry. Next, mitochondrial function and morphology were observed using Jc-1 staining, seahorse assay, western blotting, MitoTracker staining, and transmission electron microscopy. Moreover, open field test, elevated plus test, and Morris water maze were applied for animal behavior. Results Results revealed that HAH disrupted mitochondrial function and promoted neuronal apoptosis and necroptosis both in HT-22 cells and in mouse hippocampal neurons. Moreover, the mitochondrial membrane potential and adenosine triphosphate production decreased in neurons after HAH, while oxidative stress and mitochondrial fission increased. Behavioral studies suggested that HAH induced anxiety-like behavior and impaired spatial memory, while it had no effect on athletic ability. Discussion These findings demonstrated that HAH promotes mitochondrial dysfunction and apoptosis of mouse neurons, thus providing new insights into the role of mitochondrial function and neuronal cell death in acute high-altitude cerebral hypoxia.